Literature Review : Alih Kode dan Campur Kode pada Artikel 2019-2023 - Celshy Audrielia Rahman; Bambang Riadi; Rahmat Prayogi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to provide a comprehensive analysis of language switching and code-mixing across various social contexts. By exploring existing theories, models, and factors, this study seeks to understand the underlying mechanisms driving these linguistic phenomena. Furthermore, this research will examine the impact of emerging trends, especially in social media, on the study of language in multilingual communities. This research is expected to contribute significantly to our knowledge of the role of language in shaping social interactions.